Symmetry of spin–orbit torque induced meron annihilation - Jiang, Siyuan; Gao, Nan (Applied physics letters, 2024)
Electrical manipulation of the topological charges of magnetic vortices is of vital importance for the development of vortex-based devices. Here, we show that the spin–orbit torque (SOT) effect can be employed to deterministically and selectively annihilate the vortex core, and this process exhibits a symmetry that is consistent with that of the SOT-induced magnetization switching in perpendicularly magnetized systems. By changing the SOT current pulse direction, it is also possible to write back a vortex with random topological charges from the quasi-single-domain state after annihilation. These intriguing results can be utilized as a random topological charge generator and applied in stochastic computing where a tunable random stream source plays a central role.